Pendampingan Penggunaan OpenSID untuk Meningkatkan Transparansi dan Akuntabilitas Pelayanan Publik Desa - Khilda Nistrina; Sukiman Sukiman; Sutiyono Sutiyono (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2025)
The low efficiency of services and lack of public information transparency at the village level remain key challenges in achieving good governance. These issues are generally caused by limited digital literacy and suboptimal data and information management. To address these challenges, this community service activity aims to enhance the capacity of Bojongsoang Village officials in using OpenSID, a village information system that supports transparency and accountability in public services. The program was carried out in three stages: pre-implementation (coordination and needs assessment), implementation (technical training on OpenSID usage), and post-implementation (evaluation and follow-up assistance). The results showed an improvement in the officials' skills in operating the village information system, along with enhancements in administrative service quality. Strengthening digital capacity through a participatory approach has proven to be effective in supporting the realization of more effective, transparent, and accountable village governance.